Application of keyword searchable encryption in cloud - Peng LIN; Jie JIANG; Tie-ming CHEN (Tongxin xuebao)
Recently,some schemes combined keyword searchable encryption with attribute based encryption,solved access control problem in cloud environment,but they didn’t consider security problems like keyword guessing attack and security channels,so they couldn’t be applied to cloud.A keyword searchable attribute based encryption scheme with a designated tester was proposed,which could be against online/offline keyword guessing attacks and without security channel.Moreover,the user was able to encrypt data by setting a fine-gained access control policy.The efficiency of the scheme is analyzed it can be applied to cloud.